Evaluation of the susceptibility of the terrain for movements mass. Case study analysis: microbasin river Timbío – Cauca: Case study analysis: microbasin river-Timbío (Revista de Investigaciones Universidad del Quindío, 2020)
In this research paper assessed the susceptibility of the terrain before mass movements in the microbasin of the Timbío River – Cauca, using a mixed methodology based on surveys, interviews, structuring of cartographic information and spatial modeling with the bivariate method. The main results of the research indicate that high levels of susceptibility are distributed throughout the microbasin, and for the period between 2012-2018, mass movements were registered that have caused structural and environmental damage. the results obtained in the research constitute a base input to strengthen the planning processes, thus directing the actions of the community and institutions towards local risk management.
Keywords: Hazard; Disaster risk management; Microbasin; Mass movements; Susceptibility